Aktivitas Antioksidan Ekstrak Aloe vera sebagai Penangkal Radikal - Dewi Y.S.K.; Tranggono Tranggono; Sri Raharjo; Pudji Hastuti (agriTECH, 2005)
Antiradical activity of Aloe vera extracts was studied in vitro systems. Cloudy and Clarified of Aloe vera extracts exhibited marked activity on inhibition of linoleic acid peroxidation. At a concentration of 0,15 mg, Cloudy extracts exhibited higher antioxidant activity (60,16 %) than Cloudy extracts (53,30 %). Moreover, the antioxidant activity of Clarified extracts was increased affected by the concentation in the system. Increasing the concentration of Cloudy extracts up to 0,60 mg in the system did nor alter of antoxidant activity (P 50,05). Increasing' of the concentration of activated carbon (0,00 to 0,50 % and 1,00 to 2,00 %) used for clarification of Aloe vera was produced significanly decrease in scavenging 1,1-dipheny1-2- pictylhydrazyl (DPPH) free radical activity. Scavenging of free radical activity of Cloudy extracts was not affected by the concentration of extract in the system. Increasing the concentration of Clarifed Aloe vera extracts from 2,50 mg to 5,0 mg. in liposome systems was produced significantly higher of inhibitory malondyaldehyde formation than the concentration of 0,50 mg and 1,25 mg (P :50,05). Base of these results, termination of free radical reactions in Cloudy and Clarified of Aloe vera extracts is responsible for the antioxidant activity of Aloe vera extracts.